Review of Fatigue Assessment Methods for Welded Steel Structures - Boris Fuštar; Ivan Lukačević; Darko Dujmović (Advances in Civil Engineering)
Due to high stress concentrations, welded joints represent the most common locations of fatigue crack initiation in steel structures that are prone to fatigue. Welding affects material properties by the process of heating, cooling, and combining basic and additional material. Since welding is the primary process of joining elements in steel structures, it is obvious that fatigue assessment during the design and maintenance process becomes inevitable. There are many fatigue assessment methods of welded joints, but their precision remains questionable. This paper represents a review of the most common fatigue assessment methods used for welded steel joints. As a result of this review, areas that require additional research are highlighted.